1996
DOI: 10.1063/1.116486
|View full text |Cite
|
Sign up to set email alerts
|

Metalorganic chemical vapor deposition of ferroelectric SrBi2Ta2O9 thin films

Abstract: Structural and ferroelectric properties of the caxis oriented SrBi2Ta2O9 thin films deposited by the radio frequency magnetron sputtering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(69 citation statements)
references
References 9 publications
6
63
0
Order By: Relevance
“…The remanent polarization (2 P r ) of the capacitor is 27Ϯ1 C/cm 2 at an applied voltage of 10 V. This value is significantly higher than that of 8.3 C/cm 2 for SrBi 2 Ta 2 O 9 , another fatigue-free FE material. 15 The present 2 P r value is even higher than the value of 24 C/cm 2 for the PLD-grown BLT films reported by Park et al 9 The coercive field (E c ) of the BLT capacitor is in the range of 50-75 kV/cm, which is comparable to the previously reported value of 50 kV/cm for the PLD-grown capacitor. 9 More importantly, these values, i.e., P r and E c , of the capacitor ͑with an electrode area of 10 Ϫ4 cm 2 ͒ are constant throughout the whole area of the film, which presumably results from the homogeneity of the grain orientation in the present MOSD-derived film.…”
supporting
confidence: 58%
“…The remanent polarization (2 P r ) of the capacitor is 27Ϯ1 C/cm 2 at an applied voltage of 10 V. This value is significantly higher than that of 8.3 C/cm 2 for SrBi 2 Ta 2 O 9 , another fatigue-free FE material. 15 The present 2 P r value is even higher than the value of 24 C/cm 2 for the PLD-grown BLT films reported by Park et al 9 The coercive field (E c ) of the BLT capacitor is in the range of 50-75 kV/cm, which is comparable to the previously reported value of 50 kV/cm for the PLD-grown capacitor. 9 More importantly, these values, i.e., P r and E c , of the capacitor ͑with an electrode area of 10 Ϫ4 cm 2 ͒ are constant throughout the whole area of the film, which presumably results from the homogeneity of the grain orientation in the present MOSD-derived film.…”
supporting
confidence: 58%
“…Recent studies have reported that these bismuth-layered materials have presented good ferroelectric properties. 1,2 Several preparation methods of Bi-layer thin films such as laser ablation, 1,3,4 sputtering, 5 metalorganic chemical vapor deposition (MOCVD), [6][7][8] sol-gel, 9,10 and metalorganic decomposition, [11][12][13] have been employed. Normally, physical methods have the disadvantage of requiring sophisticated and expensive equipment.…”
Section: Introductionmentioning
confidence: 99%
“…͓S0003-6951͑97͒03034-9͔ SrBi 2 Ta 2 O 9 is one of the leading candidate material for ferroelectric random access memory ͑FRAM͒ devices. [1][2][3] However, the realization of a commercially viable nonvolatile FRAM technology based on SrBi 2 Ta 2 O 9 has been hampered by problems related to high processing temperature ͑Ͼ750°C͒, low P r , and low Curie temperature which make the direct integration into high density CMOS devices extremely difficult. 4 The high crystallization temperature poses a problem for the selection of a suitable barrier layer, and low P r and low T c make these films unsuitable for high density memories and high temperature operation.…”
mentioning
confidence: 99%